Experimental Study on Citrus Pre-harvest Fruit Drop in Three Major Citrus Growing Areas in Ashanti Region, Ghana - P. Y. Adjei; D. A. Boakye; C. Kwoseh; B. K. Maalekuu; E. A. Ogyiri (Research Highlights in Agricultural Sciences Vol. 3, 2022)
Citrus pre-harvest fruit loss has been a significant issue for citrus farmers in the Ashanti region. Commercial citrus fields were visited, and an anticipated one hectare (1 ha) of fruits dropped per the major citrus season prior to harvesting of both the late Valencia and red blood kinds used. Estimates were made from mid-August to mid-September 2015 for the red blood variety and from mid-December 2015 to mid-January 2016 for the late valencia. Twelve trees from each kind were chosen in each farm using a grid system in order to count or estimate the dropped fruits. In each district, sixty (60) trees of each kind were used. In all three of the citrus growing regions, there was a noticeable difference in the decline between the red blood variety and late Valencia. In Ahafo Ano South, the highest means for red blood variety and late valencia were both reported at 228 and 109, respectively. In the locations, red blood variety fell as much as twice as late Valencia. Of the two kinds, Adansi North had the least unpleasant fruit drop. Despite the fact that there were no statistically significant variations in the total mean drop among the districts, farmers in Adansi North had a better propensity to limit fruit loss, presumably through a variety of agronomic treatments. Although Ahafo Ano South’s soil pH appeared to be ideal, it had the least zinc content when it came to valencia and red blood oranges. Despite the fact that potassium levels were fairly low in all the districts, this may have prevented the district from seeing additional fruit declines.